People who seem disgusting seem more immoral - Laurent, Sean M.; Li, Jieming (Frontiers in Psychology, 2024)
Despite unresolved questions about replicability, a substantial number of studies find that disgust influences and arises from evaluations of immoral behavior and people. Departing from prior emphases, the current research examines a novel, related question: Are people who are viewed as disgusting (i.e., people whose habits seem disgusting) perceived as more immoral than typical or unusual people? Four experiments examined this, also exploring the downstream impacts of moral character judgments. Adults who seemed disgusting were regarded as more immoral for purity and non-purity violations (Experiment 1) and less praiseworthy for prosocial acts (Experiment 2). In Experiment 3, an 8-year-old with typical (but seemingly disgusting) habits was rated as “naughtier” and likelier to misbehave than an atypical child who loved vegetables and disliked sweets. Experiment 4 revealed how, when no behavioral information is available, beliefs about target disgust influence beliefs about future behavior, helping explain why seemingly disgusting targets are viewed as more immoral, but not always more punishable for their bad behavior.